Reservas internacionais ótimas de um país: um estudo do caso brasileiro - Nevares, Mario Maia (2007)
The objective of this paper is to analyze the foreign reserves accumulation among countries such Brazil that builds up international reserves to be protected from externai crises as well as to diminish such probability. We desire to analyze also the determination of optimal levei of reserves. We will approach brief historical of the literature of reserves holdings. In the study of Brazil, we will discuss the optimal levei of Brazilian international reserves using buffer stock model, with temporaries series approach, differing from previous cross-section studies.